Urban residents' attitudes towards the impact of public spaces on urban life quality: the case of Adana - Cilek, Muge Unal; Altunkasa, Mehmet Faruk; Uslu, Cengiz (Emerald Group Publishing Ltd, 2024)
PurposePublic spaces, which offer opportunities for social, cultural and recreational activities, enhance urban life quality (ULQ). Thus, this study aims to investigate the impact of public spaces and physical-environmental criteria affecting the usability of ULQ in Adana city, Turkey.Design/methodology/approachThe study method consists of three stages. Firstly, public spaces and physical-environmental criteria that can be effective in ULQ were determined. Secondly, the effect of the determining criteria on ULQ was evaluated through a 5-point Likert scale questionnaire (1 = very negative, 5 = very positive). The survey was conducted with 601 people in the four central districts of Adana, including cukurova, Seyhan, Saricam and Yuregir. Participants evaluated ULQ for both the residence district and Adana city. Lastly, factors affecting ULQ were determined using exploratory factor analysis (EFA). In addition, MANOVA was used to determine the changes in factors according to socio-demographic characteristics.FindingsBased on the EFA, the results show that the criteria affecting the ULQ are grouped into four factors, including (1) open spaces, (2) cultural, sports and recreation, (3) environmental and (4) transportation. In evaluating these factors, while gender does not affect the perception of ULQ, residence districts show a statistically significant difference in the perception of ULQ. Cultural and transportation factors show statistical differences according to education and age.Research limitations/implicationsThis study has a limitation in that it relies solely on the quantitative perceptions of residents with varying demographics, such as age, gender and educational level, to evaluate public spaces and physical environment criteria. While these perspectives are valuable, they may not necessarily reflect the qualitative reality of the urban environment. Therefore, future studies combining quantitative and qualitative data could provide a more comprehensive understanding of the factors affecting ULQ in urban areas.Social implicationsThe implementation of the survey showed the subjective perception of ULQ in Adana city. Urban green spaces, including cultural, sports and recreational areas, should be improved in areas with insufficient facilities that affect the quality of urban life. Additionally, the impact of climate conditions on the quality of life should be taken into account when designing the city to ensure maximum utilization of public spaces. Furthermore, safe cycling transportation networks should be developed.Originality/valueThe novelty of this study lies in its unique approach to investigating the effects of public spaces and physical environmental criteria on ULQ based on combining residents' perceptions, literature review and data analysis. The study provides a valuable perspective often overlooked in urban planning research, especially in developing countries like Turkey. Additionally, the study's findings can inform the development of strategies to enhance ULQ.
Keywords: Urban life quality; Urban public spaces; Exploratory factor analysis (EFA); MANOVA; Adana city